High-throughput screening for human collagenase 1 inhibitors - Ye Qi-Zhuang; Nan Fa-Jun; Hu Liang-Yan; Qian Zhen; Qian Jing (Acta Pharmacologica Sinica; Vol 21, No 11 (November 2000): Acta Pharmacologica Sinica, 2016)
"AIM: To establish a high-throughput method for inhibitor screening using a recombinant collagenase catalytic domain. METHODS: Human collagenase 1 catalytic domain protein was expressed in E coli and used for screening a set of 2720 compounds in a high-throughput fashion. RESULTS: The screening was accomplished within 2 h and 10 min with consumption of each compound at 4 micrograms. Sixty-six compounds were identified with > 60% inhibitory activity at 20 mg/L, among which 44 compounds were confirmed by subsequent testing at multiple concentrations. The most potent compound showed an IC50 at 4.3 mumol/L, and there were total 15 compounds with IC50 less than 20 mumol/L. CONCLUSION: The high-throughput method using the recombinant collagenase is fast, effective and practical in identifying inhibitors."